Third Five Year Plan Assam Review of Progress for 1962-63 - Planning Commission (Planning Commission, 1963)
But notwithstanding all these, the corrective efforts have never slackened, and in fact, have been geared up to meet the crisis, external or otherwise. Agriculture tended to be more diversified—production of crops hitherto neglected like minor grains, oil seeds, potato and vegetables recorded significant increases. The efforts in the public sector have been intensified and the progress of implementation of vital public sector schemes like power and transport has been accelerated and schemes which have been delayed or left out by the private sector have been taken over to the public sector.
Planning and Development Department, Government of Assam